2016
DOI: 10.7717/peerj.2827
|View full text |Cite
|
Sign up to set email alerts
|

Culturable bioaerosols along an urban waterfront are primarily associated with coarse particles

Abstract: The source, characteristics and transport of viable microbial aerosols in urban centers are topics of significant environmental and public health concern. Recent studies have identified adjacent waterways, and especially polluted waterways, as an important source of microbial aerosols to urban air. The size of these aerosols influences how far they travel, their resistance to environmental stress, and their inhalation potential. In this study, we utilize a cascade impactor and aerosol particle monitor to chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…Prospero et al [19] found that NSBCP concentrations were 2-3 orders of magnitude lower in selectively sampled marine air than those sampled at an island only a short distance inland. Montero et al [11] reported that the offshore and onshore total culturable microbial counts were 778 CFU m −3 and 580 CFU m −3 , respectively. Because different sources can cause microbial composition to be different and marine bacteria grow selectively on saline growth media, these previous reports may not meaningfully account for bacteria from ocean waters.…”
Section: Comparison With Literature Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Prospero et al [19] found that NSBCP concentrations were 2-3 orders of magnitude lower in selectively sampled marine air than those sampled at an island only a short distance inland. Montero et al [11] reported that the offshore and onshore total culturable microbial counts were 778 CFU m −3 and 580 CFU m −3 , respectively. Because different sources can cause microbial composition to be different and marine bacteria grow selectively on saline growth media, these previous reports may not meaningfully account for bacteria from ocean waters.…”
Section: Comparison With Literature Datamentioning
confidence: 99%
“…At present, however, the concentrations and size distributions of airborne bacteria in different regions of the Earth are not well characterized [2]. Most studies on the concentrations of airborne bacteria have been carried out in continental areas, with a handful in coastal regions [6][7][8][9][10][11]. There are only a few studies measuring bacterial concentrations in marine air, and even fewer over polar waters [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…For example Montero et al [47] reported that during summer season wind speed and total coarse bioaerosols were significantly correlated. Wind velocity is clearly associated with the release and dispersal of spores, although its effect varies according to its intensity and the height at which it is recorded.…”
Section: The Influence Of Wind Velocitymentioning
confidence: 99%
“…As found by Lighthart et al [65] and discussed by Montero et al [10], once a microbial aerosol is produced, a vertical downwind size fractionation should occur as larger particles settle out more quickly than smaller particles. Given the 3+ km fetch over Flushing Bay and NY Harbor waters, this should result in a decrease in urban terrestrial and background aerosol contributions in waterfront samples, and an increased representation of local aquatic bacteria.…”
Section: Increased Wind Speeds Strengthen Water-air Microbial Connectionmentioning
confidence: 76%